Comparison of the Effects of Eight Weeks of Moderate-Intensity Circuit Training and Morning Exercise on the Mental Health - Ahmadi, Ali; Zarali, Mohammadreza; Ebdalifar , Amin (Mental Health and Lifestyle Journal, 2026)
The purpose of this study was to compare the effects of eight weeks of moderate-intensity circuit training with morning exercise on the mental health. This study was a semi-experimental design with pretest–posttest and control and experimental groups using a pretest–posttest and control-group structure. The statistical population consisted of all permanent staff and trainees undergoing training courses at the Artillery and Missile Training Center of the Ground Forces. The sample size was determined based on inclusion criteria and using G*Power software as 45 participants (effect size = 0.45, statistical power = 0.95, significance level = 0.05), who were randomly assigned into two experimental groups and one control group (15 participants per group). The research instrument was the 28-item Goldberg General Health Questionnaire (1972). The intervention protocol in both experimental groups included five training sessions per week for 30 minutes per session at 60–90% of maximum heart rate (HR) for both types of protocols. All statistical analyses were conducted using SPSS version 25, with the significance level set at P < .05. The findings showed that the posttest mean scores of both experimental groups differed significantly from the control group in terms of mental health (p ≤ .001); however, there was no significant difference between the two experimental groups (p ≥ .001). Additionally, the effect sizes of all variables in the morning exercise group were greater than those in the circuit training group. The findings indicated that both circuit training and morning exercise programs led to significant improvement in the mental health of the permanent staff of the Ground Forces; however, morning exercise demonstrated greater effectiveness. The appropriate intensity, regular structure, and higher alignment of morning exercise with the psychological and occupational needs of military personnel resulted in stronger positive effects on reducing tension, improving mood, and enhancing psychological indicators.